Risk of prostate cancer diagnosis and mortality in men with a benign initial transrectal ultrasound-guided biopsy set: a population-based study. Issue 2 (February 2017) - Klemann, Nina; Røder, M Andreas; Helgstrand, J Thomas; Brasso, Klaus; Toft, Birgitte G; Vainer, Ben; Iversen, Peter
Summary: Background: The risk of missing prostate cancer in the transrectal ultrasound-guided systematic biopsies of the prostate in men with suspected prostate cancer is a key problem in urological oncology. Repeat biopsy or MRI-guided biopsies have been suggested to increase sensitivity for diagnosis of prostate cancer, but the risk of disease-specific mortality in men who present with raised prostate-specific antigen (PSA) concentration and a benign initial biopsy result remains unknown. We investigated the risk of overall and prostate cancer-specific mortality in men with a benign initial biopsy set. Methods: Data were extracted from the Danish Prostate Cancer Registry—a population-based registry including all men undergoing histopathological assessment of prostate tissue. All men who were referred for transrectal ultrasound-guided biopsy for assessment of suspected prostate cancer between Jan 1, 1995, and Dec 31, 2011, in Denmark were eligible for inclusion. Follow-up data were obtained on April 28, 2015. The primary endpoint was the cumulative incidence of prostate cancer-specific mortality, analysed in a competing risk setting, with death from other causes as the competing event. Findings: Between Jan 1, 1995, and Dec 31, 2011, 64 430 men were referred for transrectal ultrasound-guided biopsy, of whom 63 454 were eligible for inclusion. Median follow-up was 5·9 years (IQR 3·8–8·5) and the total follow-up time, from the enrolment of the first patient on Jan 1, 1995, until the extraction of causes of death on April 28, 2015, was 20 years. 10 407 (30%) of 35 159 men with malignant initial biopsy sets died from prostate cancer, compared with 541 (2%) of 27 181 men with benign initial biopsy sets. Estimated overall 20-year mortality was 76·1% (95% CI 73·0–79·2). In all men referred for transrectal ultrasound-guided biopsy, the cumulative incidence of prostate cancer-specific mortality after 20 years was 25·6% (24·7–26·5) versus 50·5% (47·5–53·5) for mortality from other causes. In men with benign initial biopsy sets, the cumulative incidence of prostate cancer-specific mortality was 5·2% (3·9–6·5) versus 59·9% (55·2–64·6) for mortality from other causes. In men with PSA concentrations 10 μg/L or lower and benign initial biopsy sets (2779 men), the cumulative incidence of prostate cancer-specific mortality was 0·7% (0·2–1·3). Cumulative incidence of prostate cancer specific mortality in men with benign initial biopsy sets was 3·6% (95% CI 0·1–7·2) for men with a PSA higher than 10 ng/mL but 20 ng/mL or less (855 men) and 17·6% (12·7–22·4) and for men with a PSA higher than 20 ng/mL (454 men). Interpretation: The first systematic transrectal ultrasound-guided biopsy set holds important prognostic information. The 20-year risk of prostate cancer-specific mortality in men with benign initial results is low. Our findings question whether men with low PSA concentration and a benign initial biopsy set should undergo further diagnostic assessment in view of the high risk of mortality from other causes. Funding: Capital Region of Denmark's Fund for Health Research, Danish Cancer Society, Danish Association for Cancer Research, and Krista and Viggo Petersen's Foundation.